(untitled) (The Review of Diabetic Studies, 2024)
Background: Nosocomial infections, or healthcare-associated infections (HAIs), present a significant global challenge to patient safety, clinical outcomes, and healthcare costs. Nurses, as primary frontline providers, play a pivotal role in infection prevention and control (IPC) through evidence-based practices and leadership. This review aims to comprehensively examine best nursing practices for infection control to reduce the incidence and impact of HAIs. Methods: A comprehensive literature synthesis was conducted evaluating current evidence on nursing-led IPC interventions, barriers to optimal implementation, and strategies to enhance nursing education and leadership in infection control. Focus areas included hand hygiene, PPE, aseptic technique, environmental cleaning, device-associated infection prevention, surveillance, behavioral interventions, and emerging technologies. Results: Effective nursing practices center on stringent hand hygiene compliance guided by WHO protocols, proper PPE utilization, aseptic maintenance during invasive procedures, and environmental sanitation. Continuous education, simulation training, behavioral change frameworks, and mentorship improve compliance and safety culture. Advances in surveillance, rapid point-of-care diagnostics, and artificial intelligence support early detection and antimicrobial stewardship. Multidisciplinary collaboration and strong nursing leadership drive accountability and sustainable IPC outcomes. Conclusions: Clinical nursing is fundamental to reducing healthcare-associated infections through comprehensive infection control practices, education, leadership, and innovation. Addressing current and emerging challenges requires ongoing commitment to evidence-based IPC, integrated technologies, and fostering a culture of safety and accountability within healthcare teams.